EVALUASI SARANA PRASARANA PENUNJANG KESIAPSIAGAAN GEDUNG A UNIVERSITAS SEMARANG TERHADAP RESIKO BENCANA KEBAKARAN - Ahmad Hakim Bintang Kuncoro; Talitha Zhafira (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2020)
Fire disaster is one of the disasters that is very detrimental to the community both in terms of casualties and property and assets that are invaluable. Building A University of Semarang (USM) and the assets in it are very important things to maintain. Several USM buildings have been equipped with facilities regarding fire preparedness, but most of the USM buildings also do not have these facilities completely. Apart from the facilities, the building occupants' knowledge of fire disaster preparedness cannot yet be known to what extent their understanding is. Evaluation of infrastructure which refers to the standards set by the government needs to be carried out. This can increase awareness and can also minimize losses that can occur. So that activities that take place in the USM area can run well and calmly. There is a significant relationship with a strong enough to strong and positive direction correlation level between the combination of the relationship between 2 variables consisting of HR, Program, and Facilities variables. The residents of building A USM are considered to be ready to face the risk of fire disasters, although the current condition of supporting facilities for fire disaster preparedness is deemed necessary to be added. Keywords: fire disaster, preparedness, building A USM.